2012
DOI: 10.14742/ajet.868
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of learning management system use in a South African open and distance learning institution

Abstract: The study on which this article reports examined the determinants of usage of an online learning management system (LMS) by fourth level business students at a South African open and distance learning university using an extension of the widely used technology acceptance model (TAM) as a theoretical basis. A survey was conducted among students at their annual summer school, with 213 usable questionnaires being returned. The findings suggest that perceived usefulness and perceived ease of use as core aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…The adoption and use of various e-learning systems such as Moodle, Sakai, and Blackboard to enhance teaching and learning are gaining popularity in higher education in sub-Saharan Africa (Ssekakubo, Suleman, & Marsden, 2011;Unwin et al, 2010;Venter, van Rensburg, & Davis, 2012). Countries such as Kenya, Mozambique (Unwin et al, 2010), Uganda (Mayoka & Kyeyune, 2012), Sudan (Elmahadi & Osman, 2013), Zimbabwe (Chitanana, Makaza, & Madzima, 2008), South Africa (Bagarukayo & Kalema, 2015;Venter et al, 2012), and Tanzania (Lwoga, 2012;Mtebe, Dachi, & Raphael, 2011) have adopted e-learning systems of various kinds. For instance, Moodle has 81,397 active sites registered from 234 countries (Moodle, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adoption and use of various e-learning systems such as Moodle, Sakai, and Blackboard to enhance teaching and learning are gaining popularity in higher education in sub-Saharan Africa (Ssekakubo, Suleman, & Marsden, 2011;Unwin et al, 2010;Venter, van Rensburg, & Davis, 2012). Countries such as Kenya, Mozambique (Unwin et al, 2010), Uganda (Mayoka & Kyeyune, 2012), Sudan (Elmahadi & Osman, 2013), Zimbabwe (Chitanana, Makaza, & Madzima, 2008), South Africa (Bagarukayo & Kalema, 2015;Venter et al, 2012), and Tanzania (Lwoga, 2012;Mtebe, Dachi, & Raphael, 2011) have adopted e-learning systems of various kinds. For instance, Moodle has 81,397 active sites registered from 234 countries (Moodle, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also found low usage or non-use of these systems in various institutions in countries such as Uganda (Mayoka & Kyeyune, 2012), Kenya, Zambia (Ssekakubo et al, 2011), Tanzania (Mtebe & Raisamo, 2014), and Zimbabwe (Chitanana et al, 2008;Dube & Scott, 2014). Studies have pointed out inadequate technical support, poor Internet connectivity, lack of e-learning policies, high costs of technology, and poor technological infrastructure as inhibitors to the use of these systems (Mlitwa & Van Belle, 2011;Ssekakubo et al, 2011;Unwin et al, 2010;Venter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coming to Africa, Sub-Saharan African countries, although the number of e-learning technology adoption and use is low, but several HLIs in different countries are continuing to adopt and use some LMS [1,9]. For instance, at University of South Africa (UNISA), myUnisa web application is used for collaboration and interaction and the university tutors use Sakai platform for dissemination materials and facilitating the interaction with their learners, while the mobile technology is kept for learners' communications [1,10]. Additionally, other HLIs use the LMS for complimenting the face-to-face T/L approaches, for instance, "The University of Johannesburg (UJ) which has over 45,000 full-time, parttime, face-to-face learners spread across seven campuses.…”
Section: A Hlis and Ict Adoption And Integration In T/lmentioning
confidence: 99%
“…Examples include Poll Everywhere [19] and Top Hat Monocle [20] and these offer real-time capabilities including the ability to gauge student comprehension during lectures. In addition, the latter offers features such as the grading of student activities, thus providing a competing service with that offered by the LMS.…”
Section: Drivers Of Changementioning
confidence: 99%